Energy harvesting systems in logistics - Nagy, Sándor; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2025)
Energy efficiency is also playing an increasing role in logistics systems. But to join the global trend, knowledge of existing technologies is essential. Today, it is no longer enough for an asset to be low-consumption; it is also necessary to use the energy that is lost. To choose the right solution in a given area, it is essential to know the technological background, its advantages, disadvantages and conditions of applicability. In this publication we describe the most common energy harvesting systems and their applications. We examine the solutions used in logistics systems and the areas where energy harvesting systems can be introduced and applied. We will examine future application possibilities that contribute to a more efficient use of energy